Implementation and integration of information and innovative technologies in musical training of an elementary school teacher - Odintsova, S.A.; Garkusha, K.G.; Mikhailova, N.B. (Европейский научный журнал «European Applied Sciences», 2016)
The article deals with the current issues of integrating information and innovative technologies and explicates the necessity to develop and introduce designer innovative programming and information complex into the academic process of universities as a digital content which will provide innovative and information subject matter of musical training for future elementary school teachers.
Keywords: technologies; information technologies; innovative technologies; higher education; teacher’s professional training; elementary school teacher; educational process; automated training program; electronic manual; electronic textbook